Predictors of secondary revascularization after coronary artery bypass graft surgery and role of dual antiplatelet therapy - Iftikhar Ali Ch; Khurram Nasir; Azhar Chaudhry; Pei-Tzu Wu; Muhammad Siddique; Raja Ullah; Mashal Tahirkheli; Abdul Qadar; Hunter Weitzel; Rahat Jamal; Naeem Tahirkheli (Journal of Cardiothoracic Surgery)
Abstract Background Despite advancements in surgical techniques, interventional procedures, novel pharmacotherapies, and other contemporary treatments, patients after coronary artery bypass graft surgery (CABG) remain at risk for graft failure and progression of native vessel disease progression. Consequently, secondary revascularization is often required. Methods This is a retrospective observational study evaluating the incidence, trends, and predictors of revascularization after CABG surgery. Results Of 2,476 patients followed in this post-CABG study, 1458 patients received dual antiplatelet therapy (DAPT) compared to 1005 patients received aspirin monotherapy (AMT). The overall incidence of revascularization was significantly higher in the DAPT group (14.54%, 212 out of 1458) compared to the AMT group (7.07%, 71 out of 1005), with an odds ratio (OR) of 2.24 (95% CI: 1.69–2.97, p < 0.001). 770 patients who received DAPT for six months or more after surgery were compared in sub-analysis and were noted to have significantly higher incidence of revascularization compared to AMT (22.08% vs. 6.96%; OR = 3.157, 95% CI: 2.734–4.940; p < 0.001). The binary regression model revealed that younger patients ( hazard ratio (HR) = 0.964, 95% CI: 0.95–0.97; p < 0.001), diabetics (HR = 1.50, 95% CI: 1.12-2.00, p = 0.007), patients who had fewer internal mammary artery grafts (HR = 0.54, 95% CI: 0.36–0.81, p = 0.003), and patients receiving DAPT of any duration after CABG (HR = 3.47, 95% CI: 2.55–4.72, p < 0.001) were more likely to receive revascularization after CABG. The model, comprising these four predictors, was able to explain 12.8% of the variance in post-CABG revascularization (Nagelkerke R² = 0.128; p < 0.001). The survival rates were 96.5% for the DAPT group and 92.0% for AMT (odds ratio (OR) = 0.421, 95% confidence interval (95% CI): 0.269–0.658; p < 0.001). Conclusion Diabetes mellitus, younger age, fewer Internal mammary artery grafts, and the use of DAPT after CABG were strong predictors of the need for secondary revascularization.